Does manure management affect the latent greenhouse gas emitting potential of livestock manures?. (December 2015) - Pratt, Chris; Redding, Matthew; Hill, Jaye; Jensen, Paul D.
Highlights: Manures are being increasingly sought as fertilisers. Manures are a greenhouse gas (GHG) source. It is currently thought their GHG emitting potential decreases during storage. Our research on manures from 4 livestock industries showed this is not always true. Efforts to harness manure nutrients need to account for their GHG emission risk. Abstract: With livestock manures being increasingly sought as alternatives to costly synthetic fertilisers, it is imperative that we understand and manage their associated greenhouse gas (GHG) emissions. Here we provide the first dedicated assessment into how the GHG emitting potential of various manures responds to the different stages of the manure management continuum (e.g., from feed pen surface vs stockpiled). The research is important from the perspective of manure application to agricultural soils. Manures studied included: manure from beef feedpen surfaces and stockpiles; poultry broiler litter (8-week batch); fresh and composted egg layer litter; and fresh and composted piggery litter. Gases assessed were methane (CH4 ) and nitrous oxide (N2 O), the two principal agricultural GHGs. We employed proven protocols to determine the manures' ultimate CH4 producing potential. We also devised a novel incubation experiment to elucidate their N2 O emitting potential; a measure for which no established methods exist. We found lower CH4 potentials in manures from later stages in their management sequence compared with earlier stages, but only by a factor of 0.65×. Moreover, for the beef manures this decrease was not significant ( P < 0.05). Nitrous oxide emission potential was significantly positively ( P < 0.05) correlated with C/N ratios yet showed no obvious relationship with manure management stage. Indeed, N2 O emissions from the composted egg manure were considerably (13×) and significantly ( P < 0.05) higher than that of the fresh egg manure. Our study demonstrates that manures from all stages of the manure management continuum potentially entail significant GHG risk when applied to arable landscapes. Efforts to harness manure resources need to account for this.